2021
DOI: 10.1016/j.jbc.2021.100524
|View full text |Cite
|
Sign up to set email alerts
|

Covalent N-arylation by the pollutant 1,2-naphthoquinone activates the EGF receptor

Abstract: The epidermal growth factor receptor (EGFR) is the most intensively investigated receptor tyrosine kinase. Several EGFR mutations and modifications have been shown to lead to abnormal self-activation, which plays a critical role in carcinogenesis. Environmental air pollutants, which are associated with cancer and respiratory diseases, can also activate EGFR. Specifically, the environmental electrophile 1,2-naphthoquinone (1,2-NQ), a component of diesel exhaust particles and particulate matter more generally, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In particular, electrophilic environmental chemicals should be given priority for evaluation not only because they are routinely and chronically exposed in daily life but also because they form protein adducts and disrupt the functions of proteins ( 78 , 79 ). We previously reported that 1,2-naphthoquinone, which is found in air pollutants such as particulate matter 2.5, activates EGFR via N -arylation and induces PI3K–Akt signaling ( 80 ). Our studies indicate that the disruption of signaling homeostasis by 1,2-naphthoquinone, MVK, and MVK analogs leads to adverse physiological effects and demonstrate the importance of protein adduct formation by environmental electrophiles as a model for exposome research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, electrophilic environmental chemicals should be given priority for evaluation not only because they are routinely and chronically exposed in daily life but also because they form protein adducts and disrupt the functions of proteins ( 78 , 79 ). We previously reported that 1,2-naphthoquinone, which is found in air pollutants such as particulate matter 2.5, activates EGFR via N -arylation and induces PI3K–Akt signaling ( 80 ). Our studies indicate that the disruption of signaling homeostasis by 1,2-naphthoquinone, MVK, and MVK analogs leads to adverse physiological effects and demonstrate the importance of protein adduct formation by environmental electrophiles as a model for exposome research.…”
Section: Discussionmentioning
confidence: 99%
“…After quantification of protein concentration by the bicinchoninic acid (BCA) assay (Takara, T930A) method, protein samples were boiled in 1×Laemmli SDS sample buffer (62.5 mM Tris–HCl [pH 6.8], 5% [v/v] 2-mercaptoethanol, 2% [w/v] SDS, and 10% [v/v] glycerol) for 5 min. The samples were subjected to SDS–PAGE and Western blotting as previously described ( 80 ).…”
Section: Methodsmentioning
confidence: 99%